The need to conserve farm animal genetic resources in Africa: Should policy makers be concerned? - Wollny, C.B.A. (Elsevier, 2003)
This paper outlines key factors contributing to the erosion of animal genetic resources and discusses strategic options for policy makers. The ratification of the Convention on Biological Diversity (CBD) in 1993 represents an international consensus to conserve biodiversity including that of farm animal genetic resources (FAnGR). In Africa, conservation of agricultural biodiversity is inbuilt into the low input–low output production strategies of smallholder farming systems. These systems are often associated with poverty in rural areas and numerous development projects have thus sought to alleviate such poverty by promoting crossbreeding or modern reproductive technologies. However, uncontrolled crossbreeding has been and remains a threat to the conservation of local farm animal populations. Objectives for the conservation of a local farm animal population and opportunities to utilise its diversity to meet present and future market demands, to serve as an insurance against environmental changes such as changes in production, socio-economic, and cultural conditions can be identified for research and development. To improve food security and to alleviate poverty through the conservation of FAnGR in Africa, utilisation of local farm animal populations depends on the ability of communities to decide on and implement appropriate breeding strategies. It is for this reason that enabling policies are required.